Shear bond strength fissure sealant based on glass ionomer after topical fluor application: a comparison between sodium fluoride and acidulated phosphate fluoride - Akwan, Yulie Emilda; Paramita, Annisa Listya; Rahmitasari, Fitria (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Application of fissure sealants to young permanent teeth is one of the preventive measures for caries in the field of dentistry. Fissure sealants based on glass ionomer cement (GIC) have the advantage of releasing fluoride. Sodium fluoride and acidulated phosphate fluoride (APF) are remineralization agents because they can increase remineralization by altering hydroxyapatite to fluorapatite and this in turn makes fluorine able to increase pH. Fluoride can prevent caries by increasing remineralization of the enamel that has just been demineralized by acids produced by plaque bacteria. The aim of this study is to compare the shear bond strength fissure sealant based on glass ionomer between sodium fluoride and APF topical fluor applicationMethod: This research applied true experimental design with post test only control group design. The 21 maxillary permanent premolars were distributed into 3 groups, namely the control group (K1), the treatment group added 5% sodium fluoride (K2), and the treatment group added 1.23% APF (K3). Result: One Way ANOVA and post hoc LSD analysis test displayed no significant difference in each group. This could be due to the material used as a conditioner prior to the GIC application. The addition of fluoride ions will inhibit the demineralization process of the enamel produced by the application of conditioner. So it does not rule out that it will interfere with the attachment of the GIC material used as a fissure sealant in this research.Conclusion: There was no significant difference in shear bond strength of fissure sealant based on glass ionomer between sodium fluoride and acidulated phosphate fluoride topical application.